Microwave glycation of soy protein isolate with rare sugar (D-allulose), fructose and glucose. (April 2021) - Namli, Serap; Sumnu, S. Gulum; Oztop, Mecit H.
Abstract: Glycation, the initial step of Maillard reaction, can be used to modify the properties of proteins. In this study, to speed up the reaction, microwave glycation of soy protein isolate (SPI) in an aqueous medium with fructose, glucose, and D-allulose (rare sugar) were performed at pH 7 and pH 10 and the results were compared with the conventional 'water bath glycation' method. The reducing sugar concentration of glycated protein was quantified by High Performance Liquid Chromatography (HPLC) experiments and the structural changes of the soy protein isolate after glycation were investigated by Fourier Transform Infrared spectroscopy (FT-IR) and Time Domain Nuclear Magnetic Resonance (TD-NMR) relaxometry. Alkaline pH was found to be more effective for microwave glycation of soy protein isolate. The reactivity of sugars for microwave glycation reaction was ordered as D-allulose > fructose > glucose. According to the results, microwave heating was found to be more effective for glycation of SPI than water bath heating. NMR relaxometry results provided valuable information about structural characteristics and water mobility in the system. Graphical abstract: Image 1 Highlights: Reactivity of the sugars for glycation was found as D-allulose > fructose > glucose. Microwave glycation of soy protein isolate was found to be more efficient than water bath glycation. Isomerization of sugars at microwave heating was observed at alkaline conditions. Structural modifications and water mobility in the system were investigated by FT-IR and NMR experiments.